PEMBELAJARAN KONTEKSTUAL PADA MATERI PERPINDAHAN ENERGI PANAS UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS KELAS IV - Dewi, Kania Kusuma; Sudin, Ali; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
In the study to see the influence of contextual approaches to students' science process skills. The method used is pre-experimental with one group pretest-posttest design. The population in this study were all students of 4thgrader SDN in kecamatan Cimanggung namely SDN Bunter 1, SDN Bunter 3, SDN Tanjungsiang. The instruments used are science skill test, observation sheet, questionnaire and interview. The result of research with significance level Î± = 0,05 shows: First, science learning using contextual approach can improve students' science process skill in superior group Second, science learning using a contextual approach can improve students' science process skills in the group Third, science teaching using contextual approach can improve students' science process skill in asor groupFourth, there is a difference in the improvement of students' science process skills in superior groups, papak, asor.